Paenibacillus mangrovi sp. nov., a novel endophytic bacterium isolated from bark of Kandelia candel. Issue 3 (8th March 2023) - Huang, Zi-Hao; Yang, Hui-Lan; Chen, Feng; Li, Fei-Na; Meng, Ling-Jie; Chen, Xiao-Hui; Chen, Ming-Sheng; Ma, Xiao; Zheng, Zhou-Qing; Tuo, Li
Abstract : A endospore-forming bacterium, designated strain KQZ6P-2 T, was isolated from surface-sterilized bark of the mangrove plant Kandelia candel, collected from Maowei Sea Mangrove Nature Reserve in Guangxi Zhuang Autonomous Region, China. Strain KQZ6P-2 T was able to grow at NaCl concentrations in the range of 0–3 % (w/v) with optimum growth at 0–1 % (w/v) NaCl. Growth occurred at 20–42 °C (optimal growth at 30–37 °C) and pH 5.5–6.5 (optimal growth at pH 6.5). The 16S rRNA gene sequence similarity between strain KQZ6P-2 T and its closest phylogenetic neighbour Paenibacillus chibensis JCM 9905 T was 98.2 %. Phylogenetic analyses using 16S rRNA gene sequences showed that strain KQZ6P-2 T formed a distinct lineage with Paenibacillus chibensis JCM 9905 T . The draft genome of strain KQZ6P-2 T was 5 937 633 bp in size and its DNA G+C content was 47.2mol%. Comparative genome analysis revealed that the average nucleotide identity, digital DNA–DNA hybridization and average amino acid identity values among strain KQZ6P-2 T and its related species were below the cut-off levels of 95, 70 and 95.5%, respec-tively. The cell-wall peptidoglycan of strain KQZ6P-2 T contained meso -diaminopimelic acid as the diagnostic diamino acid. Major cellular fatty acids were anteiso-C15:0 and C16:0 . The polar lipids comprised diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, two unidentified aminophospholipids, four unidentified phospholipids, an unidentified aminolipid and five unidentified lipids. Based on phylogenetic, phenotypic and chemotaxonomic data, strain KQZ6P-2 T represents a novel species of the genus Paenibacillus, for which the name Paenibacillus mangrovi sp. nov. is proposed. The type strain is KQZ6P-2 T (=MCCC 1K07172 T =JCM 34931 T ).